"Good" Court-Packing? The Paradoxes of Constitutional Repair in Contexts of Democratic Decay. Issue 8 (October 2022) - Daly, Tom Gerald
Abstract: U.S. debates on reforming the Supreme Court, including controversial arguments to break the norm against court-packing to repair the democratic system, have generally focused on historical precedents and the domestic system, with scant comparative analysis. However, the U.S. debate raises fundamental questions for comparative constitutional lawyers regarding the paradoxes of constitutional repair in contexts of democratic decay, framed here as a distinct category of constitutional transition. This study argues that sharpening our analytical tools for understanding such reforms requires a novel comparative and theoretical approach valorizing the experiences of Global South states and drawing on, and connecting, insights across four overlapping research fields: Democratic decay, democratization, constitution-building, and transitional justice. The article accordingly pursues comparative analysis of the legitimacy of court-packing through case-studies of Turkey and Argentina to offer a five-dimensional analytical framework: (i) democratic context ; (ii) articulated reform purpose ; (iii) reform options ; (iv) reform process ; and (v) repetition risk . In doing so, this article seeks not to present a rigid check-list for evaluating the legitimacy of contested reforms, but rather, to foreground important dimensions of reforms aimed at reversing democratic decay as an emergent global challenge for public law meriting closer attention.